Inventarization Epiphytic Mosses in Hutan Lumut Area “Dataran Tinggi Yang”, Wildlife Preserve Argopuro Mountain - Galen Rahardian; Gayut Widya Prakosa; Aswar Anas; Alhabsy Hidayatullah; Ahmad Zainul Hasan (Biotropika: Journal of Tropical Biology, 2017)
Mosses are group of non-vascular plant, small size, and able to growth in many substrates. Epiphytes are organism witch growth at wood surface of living plant. Epiphytic mosses has some advantages, there are out of   range from terestial organism and to get more optimaly sun light. One of place which has suitable conditions for this research is in Wildlife Preserve “Dataran Tinggi Yang”, Argopuro Mountain. This research purpose to get known about species of epiphyte mosses and morphological characteristic each species of epiphytic mosses in Wildlife Preserve “Dataran Tinggi Yang”, Argopuro Mountain. The result of identification and characterization obtained 17 families and 25 species of epiphytic mosses. The main characteristic of mosses are leaf position, leaf form,  and leaf costa.